Comparing China's urban systems in high-speed railway and airline networks. (April 2018) - Yang, Haoran; Dobruszkes, Frédéric; Wang, Jiaoe; Dijst, Martin; Witte, Patrick
Abstract: Although the Chinese high-speed railway (HSR) entered the transportation market at a late stage in 2003, its networks have become the world's largest and are currently even growing faster than airline networks. Using the 2013 origin/destination (O/D) passenger flow data instead of commonly used scheduled data, we compare the spatial configurations of the Chinese national urban system in both high-speed railway and airline networks. The results show that HSR-dominant cities and links are located mainly in the middle and eastern parts of China, offering regional connections, whereas air-dominant cities and links are evenly distributed across the whole of China and predominantly offer interregional connections. This is mainly because HSR networks are more focused on connections to cities with high socio-economic performance and are more restricted by the geographical distance between linked cities than the airline networks. Furthermore, HSR networks promote agglomeration economies within cities located along the trunk lines in specific regions, whereas airline networks contribute to more balanced urban development in China. These dimensions indicate that the configuration of urban systems in HSR networks differ largely from that of air networks when measured in terms of passenger flows. Highlights: We used the OD passenger flow data to compare the spatial configurations of Chinese urban system instead of commonly used scheduled data. Results show that the configuration of national urban systems in HSR networks differs largely from that in air networks. HSR networks are more focused on connections to cities with high socio-economic performance, and are more restricted by the geographical distance between linked cities.